Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Adiksi Coffee - Iskandar Ali Alam; Indriyan Prameswari Putri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze the influence of discipline and work motivation on the performance of employees at Addiction Coffee. The analytical method used is multiple regression analysis with 30 employees as respondents. The data collection is done by questionnaire or questionnaire then processed by SPSS statistical software version 29. The results show that the work discipline variable has a positive impact on the work efficiency of the employees. staff, however, this effect was not statistically significant. On the contrary, the change in work motivation was found to have a clear positive effect and play an important role in improving the working efficiency of employees at Addi Coffee. The conclusion of this study confirms that work motivation has a greater influence on employee performance than work discipline. Therefore, to improve employee performance, Adiksi Coffee can further focus on developing strategies and programs to encourage and maintain employees' high work motivation.